Manfaat Emotional Freedom Technique (EFT) Bagi Pasien Dengan Gangguan Kecemasan - Nurmawati S Lataima; Ninuk Dian Kurniawati; Puji Astuti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Psychological problems such as anxiety are one of the most common problems in the world. Handling for this anxiety problem is not adequate and requires a lot of money. Psychological intervention is needed to help patients overcome the anxiety they experience. Objective: To outline some of the benefits of the Emotional Freedom Technique (EFT) intervention that can help patients reduce anxiety Method: The database used in this study was Scopus, Google Schoolar and Pubmed was limited to the last 5 years from 2015 to 2020, full text article in English. The keywords used were "Emotional Freedom Technique", "OR", "AND", "Anxiety", "AND", "Tapping". This systematic review used 11 articles that fit the inclusion criteria. Result: The EFT intervention was an easy, inexpensive and effective intervention. The benefits of the EFT intervention were reduce depression, anxiety, stress, increase immunological levels, reduce levels of cortisol in the blood and improve quality of life. Conclusion: EFT intervention has many benefits in helping patients who experience various psychological illnesses. Suggestion: EFT can be applied in health services or applied independently. Keywords: Emotional Freedom Technique; anxiety; tapping ABSTRAK Latar belakang: Masalah psikologi seperti kecemasan menjadi salah satu masalah yang paling umum di dunia. Penanganan untuk masalah kecemasan ini belum mamadai dan memerlukan biaya yang tidak sedikit. Intervensi psikologi sangat dibutuhkan untuk membantu pasien mengatasi kecemasan yang dialami. Tujuan: Untuk menguraikan beberapa manfaat intervensi EFT yang dapat membantu pasien dalam mengurangi kecemasan. Metode: Database yang digunakan dalam penelitian ini adalah Scopus, Google Schoolar dan Pubmed terbatas 5 tahun terakhir dari 2015 hingga 2020, full text article dengan berbahasa Inggris. Kata kunci yang digunakan adalah “Emotional Freedom Technique”, ”OR”, “AND”, “ Anxiety”, “AND”, “Tapping”. Systematic review ini menggunakan 11 artikel yang sesuai dengan kriteria inklusi. Hasil: EFT merupakan intervensi yang mudah, murah dan efektif. Manfaat intervensi EFT yaitu dapat menurunkan depresi, kecemasan, stress, meningkatkan kadar imunologi, menurunkan kadar kortisol dalam darah dan meningkatkan kualitas hidup. Simpulan: EFT memiliki banyak manfaat dalam membantu pasien yang mengalami berbagai penyakit psikologi. Saran: EFT dapat diterapkan dalam pelayanan kesehatan maupun diterapkan secara mandiri. Kata kunci: Emotional Freedom Technique; anxiety; tapping